2016
DOI: 10.1111/1346-8138.13512
|View full text |Cite
|
Sign up to set email alerts
|

Biosimilars in psoriasis: Clinical practice and regulatory perspectives in Latin America

Abstract: Latin American countries view biosimilar agents as an effective approach to curtail health-care expenditures while maintaining the safety and efficacy profile of their branded innovator comparators. To understand the complexities of the regulatory landscape and key therapeutic issues for use of biosimilars to treat moderate to severe psoriasis in Latin America, the International Psoriasis Council convened dermatology experts from Argentina, Brazil, Chile, Colombia and Mexico in October 2015 to review the defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…In the USA, the FDA has specified that biosimilars should have unique nonproprietary names that are distinguished from those of their reference products by four-letter suffices which are devoid of meaning [27]. In Mexico, Colombia, Argentina, Brazil, and Chile, there is no nonproprietary naming convention to distinguish biosimilars from their reference products [28]. The World Health Organization recommends that the standard international nonproprietary name (INN) system be used for biosimilars to enable easy recognition of the active ingredient [29].…”
Section: A Naming Convention Should Be Implemented To Clearlymentioning
confidence: 99%
See 1 more Smart Citation
“…In the USA, the FDA has specified that biosimilars should have unique nonproprietary names that are distinguished from those of their reference products by four-letter suffices which are devoid of meaning [27]. In Mexico, Colombia, Argentina, Brazil, and Chile, there is no nonproprietary naming convention to distinguish biosimilars from their reference products [28]. The World Health Organization recommends that the standard international nonproprietary name (INN) system be used for biosimilars to enable easy recognition of the active ingredient [29].…”
Section: A Naming Convention Should Be Implemented To Clearlymentioning
confidence: 99%
“…Studies have estimated that the potential savings in the USA from using biosimilars over a 10-year period could range between USD $25 billion and USD $100 billion [36]. In Chile, Brazil, and Mexico, biosimilars are priced 20 to 35% lower than their reference biologics in [28]. Mestre-Ferrandiz and colleagues suggested that, as physicians become more confident about the data supporting interchangeability between biosimilars and their reference products, the prices could decrease, provided that incentives are in place for both payers and patients to benefit from price competition [37].…”
Section: A Naming Convention Should Be Implemented To Clearlymentioning
confidence: 99%
“…46,48 The term “biosimilar” is not necessarily used in each case; in Mexico, for example, “biocomparables” is the official term. 49 Other countries, such as Bolivia and Paraguay, are in the process of developing or finalizing legislation. 4648 In general, the region is moving toward increasing standards of regulation, and the WHO guidelines have been adopted or used as a basis for guidance in several instances.…”
Section: Biosimilars In Latin America: Current Situationmentioning
confidence: 99%
“…For example, in addition to a “complete dossier” pathway and a comparative pathway similar to the respective approval routes for novel biologics and biosimilars in other countries, regulations in Colombia describe a third, “abbreviated” comparative pathway via which a biologic can be evaluated. 46,49,51 The abbreviated pathway has attracted substantial criticism that it deviates markedly from international norms and does not provide certainty that a product approved by this route would have an acceptable benefit–risk profile, 46,49,52,53 although such claims have been refuted by authors in Colombia. 54,55 In another example, although Brazilian biologic approval guidelines from the Agência Nacional de Vigilância Sanitária (ANVISA) describe a comparative pathway for the approval of biosimilars akin to that in the WHO guidance, there is a lack of clarity regarding the nature of the clinical studies that are needed.…”
Section: Biosimilars In Latin America: Current Situationmentioning
confidence: 99%
See 1 more Smart Citation